2019
DOI: 10.1093/intimm/dxz074
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-34 expression in ovarian cancer: a possible correlation with disease progression

Abstract: Ovarian cancer is the second-most lethal gynecological malignancy and the seventh-commonest cause of cancer-related death in women around the world. Most of the ovarian cancer patients are diagnosed at advanced stages and suffer from recurrence after primary cytoreductive surgery and standard first-line chemotherapy. Thus, the successful management of ovarian cancer patients requires the identification of factors that contribute to progression and relapse. Interleukin-34 (IL-34) is a novel cytokine that acts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Importantly, further studies have found that IL-34 is highly expressed in ovarian cancer cells and tissues, which is associated with poor progression-free survival (PFS) and overall survival, while the expression of CSF-1 has not changed. Moreover, it's worth noting that compared with CSF-1, IL-34 has a stronger affinity for CSF1R (190). It can be seen that tumor cells may secrete high levels of IL-34 to stimulate the CSF1R signaling of TAMs to promote tumor progression.…”
Section: The Relationship Between Tumor Cells and Tams And Targeted Tmentioning
confidence: 99%
“…Importantly, further studies have found that IL-34 is highly expressed in ovarian cancer cells and tissues, which is associated with poor progression-free survival (PFS) and overall survival, while the expression of CSF-1 has not changed. Moreover, it's worth noting that compared with CSF-1, IL-34 has a stronger affinity for CSF1R (190). It can be seen that tumor cells may secrete high levels of IL-34 to stimulate the CSF1R signaling of TAMs to promote tumor progression.…”
Section: The Relationship Between Tumor Cells and Tams And Targeted Tmentioning
confidence: 99%
“…In lung cancers, IL-34 triggers activation of CCAAT/enhancer-binding protein β via AKT-mediated pathway with the downstream effect of enhancing the pro-tumorigenic and immunosuppressive functions of TAMs and consequently promoting the survival of chemoresistant cancer cells [36]. IL-34 is also expressed in human ovarian cancer cell lines and tissues [43]. IL-34 levels increase in ovarian cancer cell lines following treatment with cytotoxic agents and in the tumor tissues of chemotherapy-given ovarian cancer patients [43].…”
Section: Involvement Of Il-34 In Cancer Initiation and Progressionmentioning
confidence: 99%
“…IL-34 is also expressed in human ovarian cancer cell lines and tissues [43]. IL-34 levels increase in ovarian cancer cell lines following treatment with cytotoxic agents and in the tumor tissues of chemotherapy-given ovarian cancer patients [43]. Notably, high IL-34 expression correlates with worse progression-free survival and overall survival in different cohorts and in a mouse model of ovarian cancer [43].…”
Section: Involvement Of Il-34 In Cancer Initiation and Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes related to Treg infiltration also include the IL-related gene IL-1β, which induces Treg infiltration through the CCL22-CCR4-Foxp3 pathway and participates in the development of HNSCC (Li et al, 2019). Other IL-related genes can promote tumor metastasis (León et al, 2015;Sénécal et al, 2016;Goh and Hong, 2017;Endo et al, 2020). Growth factor-related genes are also associated with tumor metastasis, among which LTα, TNFRSF12α, TNFRSF25, TNFRSF4, and IRF9 can mediate HNSCC tumorigenesis and metastasis through the NF-κB signaling pathway (Schreiber et al, 2012;Lauenborg et al, 2015;Nan et al, 2018;Qiu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%